A 3D Lithospheric Thermal Model of the South China Sea Jointly Constrained by Heat Flow, Curie-Point Depth and S-Wave Velocity - Liang Huang; Chun-Feng Li; Zhaocai Wu; Jinyao Gao (Journal of Marine Science and Engineering, 2025)
In this study, we develop a 3D thermal model of the South China Sea (SCS) lithosphere through the joint analysis of heat flow, Curie-point depth derived from magnetic anomalies, and shear wave velocity. Results show the Moho temperature is below 250 °C in the oceanic basin but exceeds 350 °C in continental margins. We evaluate potential Moho drilling sites based on temperature, crustal thickness, water depth, and sediment thickness, identifying six favorable zones in the east sub-basin. The thermal lithosphere thickness correlates with tectonic settings in continental areas, while the oceanic lithosphere is thicker than predicted by theoretical models. Global analysis suggests that the slow spreading rate may have also contributed to the thickening of the oceanic lithosphere in the SCS.